Upaya Peningkatan Sikap dan Pengetahuan Kader Posyandu Tentang Gizi Seimbang Pada Balita Melalui Edukasi - Ihsan Kamaruddin, Muh.; Wibowo, Wibowo; Anto, Sardi; Andi Latif , Syarifuddin; Triloka Wulandari, Dewi (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2023)
Efforts to increase the role of integrated healthcare centre cadres are not only the government's responsibility but all components of society. To improve competence related to health services, weight weighing, card filling towards health, early detection of growth disorders, nutritional counseling, supplementary feeding and vitamin administration, pregnant women and puerperal mothers. Nutrition service activities for toddlers in integrated healthcare center are the main activities in implementing Integrated Healthcare Center activities. This activity aims to increase knowledge about nutrition services at Integrated Healthcare Center. The method used with leaflet media and PowerPoint about balanced nutrition education in toddlers as an evaluation was carried out pretest and posttest of participants. The activity results showed an increase in the attitude (90%) and knowledge (88%) of Integrated Healthcare Center cadres after education. Conclusion. After being given nutrition education, the cadres experienced an increase in knowledge. Actively integrated healthcare center cadres in health services are very important to improve the quality and nutritional status of balance for the community, especially maternal and child health.